Reactive hot melt adhesive composition and bonding method

JP2025023650APending Publication Date: 2025-02-17RESONAC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023127978
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、柔軟性が高く、高温高湿環境下での信頼性が高い接着が可能な反応性ホットメルト接着剤組成物及び接着方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023650000002
    Figure 2025023650000002
  • Figure 2025023650000001
    Figure 2025023650000001
Patent Text Reader

Abstract

To provide a reactive hot melt adhesive composition that is highly flexible and capable of ensuring reliable adhesion under high-temperature, high-humidity environments, and to provide a bonding method.SOLUTION: There is provided a reactive hot melt adhesive composition comprising a urethane prepolymer (A) and a hindered phenol antioxidant (B). The urethane prepolymer (A) is composed of a compound that has a structure derived from a polyol and an isocyanate group in at least any terminal of the structure derived from a polyol. The structure derived from a polyol includes a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol. The hindered phenol antioxidant (B) has a hydroxy group bonded to a benzene ring, and in the benzene ring to which the hydroxy group is bonded, a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxy group is bonded.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reactive hot melt adhesive composition and a bonding method. [Background technology]

[0002] Hot melt adhesives are suitable for improving productivity because they can bond in a short time. Hot melt adhesives can be broadly divided into two types: thermoplastic and reactive. Of these, reactive types, i.e. reactive hot melt adhesives, are widely used with polymers (urethane prepolymers) that have isocyanate groups at their ends as the main component.

[0003] After application, reactive hot melt adhesives that are primarily made of urethane prepolymers develop a certain degree of adhesive strength in a short time as the adhesive cools and solidifies. The isocyanate groups at the ends of the urethane prepolymers then react with moisture in the air or on the surface of the adherend, resulting in a high molecular weight or the formation of a cross-linked structure, which increases heat resistance. This reaction also gives reactive hot melt adhesives that are primarily made of urethane prepolymers a higher adhesive strength than hot melt adhesives that are primarily made of thermoplastic resins. Polyols are widely used as raw materials for urethane prepolymers.

[0004] For example, Patent Document 1 describes that polyols used as a raw material for a urethane prepolymer having an isocyanate group include polyether polyols, polyacrylic polyols, crystalline polyester polyols, and polycaprolactone polyols.

[0005] Patent Document 2 describes that polyols used as a raw material for a urethane prepolymer having an isocyanate group include polyether polyols, polyacrylic polyols, crystalline polyester polyols, and polycarbonate polyols. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-97650 A [Patent Document 2] JP 2020-94085 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, adhesives have come to be used as an alternative to screws, welding, etc., and adhesives are now required to have higher reliability than ever before. A representative example of high reliability is the ability to maintain adhesive strength under high temperature and high humidity conditions.

[0008] However, in the configurations of Patent Documents 1 and 2, polyester polyol is used as a raw material for the urethane prepolymer, and if left for a long period of time under high temperature and high humidity conditions, the adhesive strength is likely to decrease due to hydrolysis of the ester bonds in the urethane prepolymer.

[0009] Therefore, an object of the present invention is to provide a reactive hot melt adhesive composition and bonding method that are highly flexible and capable of providing highly reliable bonding even in high temperature and high humidity environments. [Means for solving the problem]

[0010] In order to achieve the above object, the present invention is configured as follows. [1] A reactive hot melt adhesive composition comprising a urethane prepolymer (A) and a hindered phenol-based antioxidant (B), wherein the urethane prepolymer (A) is composed of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from a polyol, the structure derived from a polyol including a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, and the hindered phenol-based antioxidant (B) is a compound having a hydroxyl group bonded to a benzene ring, and a structure in which a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded in the benzene ring. [2] The reactive hot melt adhesive composition according to [1], wherein the urethane prepolymer (A) contains two or more types of compounds each having one of a structure derived from the polycarbonate polyol and a structure derived from the polyether polyol. [3] The reactive hot melt adhesive composition according to [1], wherein the content of the hindered phenol-based antioxidant (B) is 0.10 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the urethane prepolymer (A). [4] The reactive hot melt adhesive composition according to [1] or [2], wherein the urethane prepolymer (A) contains a compound having isocyanate groups at multiple terminals. [5] The reactive hot melt adhesive composition according to [1] or [2], wherein the urethane prepolymer (A) contains a compound having isocyanate groups at two terminals. [6] The reactive hot melt adhesive composition according to [1] or [2], wherein in the urethane prepolymer (A), the proportion of the structure derived from the polycarbonate polyol in the structure derived from the polyol is 10 mass% or more and 95 mass% or less. [7] The reactive hot melt adhesive composition according to [1] or [2], wherein in the urethane prepolymer (A), a ratio of structures derived from the polyether polyol to structures derived from the polyol is 5.0 mass% or more and 90 mass% or less. [8] The reactive hot melt adhesive composition according to [1] or [2], wherein the urethane prepolymer (A) has a structure derived from a crystalline polycarbonate polyol as the structure derived from the polycarbonate polyol, and the crystalline polycarbonate polyol is a polycarbonate polyol that forms crystals at 25°C. [9] The reactive hot melt adhesive composition according to [8], wherein in the urethane prepolymer (A), the proportion of the structure derived from the crystalline polycarbonate polyol in the structure derived from the polyol is 10 mass% or more and 95 mass% or less.

[10] The reactive hot melt adhesive composition according to [1] or [2], wherein the urethane prepolymer (A) contains, as the structure derived from the polyol, a structure derived from a crystalline polycarbonate polyol and a structure derived from a liquid polyether polyol, the crystalline polycarbonate polyol is a polycarbonate polyol that forms crystals at 25°C, and the liquid polyether polyol is a polyether polyol that is neither crystallized nor vitrified at 25°C, and the proportion of the structure derived from the crystalline polycarbonate polyol in the structure derived from the polyol in the urethane prepolymer (A) is 50% by mass or more and 80% by mass or less, and the proportion of the structure derived from the liquid polyether polyol in the structure derived from the polyol is 15% by mass or more and 45% by mass or less.

[11] The reactive hot melt adhesive composition according to [1] or [2], wherein in the urethane prepolymer (A), the proportion of structures derived from the polycarbonate polyol in the structures derived from the polyol is 20% by mass or more and 60% by mass or less, and the proportion of structures derived from the polyether polyol in the structures derived from the polyol is 40% by mass or more and 80% by mass or less.

[12] A bonding method comprising the steps of: applying a molten reactive hot melt adhesive composition to a first member; attaching a second member to the surface of the first member to which the reactive hot melt adhesive composition is applied; and reacting the applied reactive hot melt adhesive composition in moisture-containing air, wherein the reactive hot melt adhesive composition comprises a urethane prepolymer (A) and a hindered phenol-based antioxidant (B), the urethane prepolymer (A) is composed of a structure derived from a polyol and a compound having an isocyanate group at at least one end of the polyol-derived structure, the polyol-derived structure including a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, and the hindered phenol-based antioxidant (B) is a compound having a hydroxyl group bonded to a benzene ring, and a structure in which a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded in the benzene ring to which the hydroxyl group is bonded. Effect of the Invention

[0011] According to the present invention, it is possible to provide a reactive hot melt adhesive composition and bonding method that are highly flexible and capable of providing highly reliable bonding even in high temperature and high humidity environments. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a plan view showing a test piece for measuring the adhesive strength of the adhesive composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Preferred embodiments of the present invention will be described in detail below, however, the present invention is not limited to the following embodiments.

[0014] A certain structure X (e.g., a structure derived from a polyol) contained in the urethane prepolymer (A) described below means a structure X possessed by a compound contained in the urethane prepolymer (A). In other words, the content of a certain structure X contained in the urethane prepolymer (A) is the total amount of structure X possessed by a compound contained in the urethane prepolymer (A). When structure X is a structure derived from a polyol, it is considered to include oxygen atoms in the urethane bond at both ends of the structure and hydrogen atoms bonded to nitrogen atoms forming the urethane bond.

[0015] The content of a certain structure X in the urethane prepolymer (A) is the mass ratio of the structure X contained in these compounds to the total mass of the compounds contained in the urethane prepolymer (A). Note that in this calculation, the structure derived from the polyol is considered to include the oxygen atoms in the urethane bonds at both ends of the structure and the hydrogen atoms bonded to the nitrogen atoms forming the urethane bonds.

[0016] [Reactive hot melt adhesive composition] The reactive hot melt adhesive composition of this embodiment (hereinafter, may be simply referred to as "adhesive composition") contains a urethane prepolymer (A) and a hindered phenol-based antioxidant (B).

[0017] [Urethane prepolymer (A)] The urethane prepolymer (A) is composed of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from a polyol. The adhesive composition according to the present embodiment contains the urethane prepolymer (A), and thus can exhibit excellent adhesiveness after moisture curing.

[0018] The content of the urethane prepolymer (A) in the adhesive composition is preferably 75% by mass or more, more preferably 88% by mass or more, and even more preferably 95% by mass or more, because when the urethane prepolymer (A) contained in the adhesive composition reacts, it has a higher molecular weight.

[0019] The urethane prepolymer (A) may contain a compound having structures derived from multiple polyols with different structures (e.g., structures derived from polyisocyanate) sandwiched between them. The urethane prepolymer (A) may contain a compound having a structure having a sequence such as isocyanate group-structure derived from polyol-structure derived from polyisocyanate-structure derived from polyol-structure derived from polyisocyanate-structure derived from polyol-isocyanate group.

[0020] The urethane prepolymer (A) preferably contains a compound having isocyanate groups at multiple ends, more preferably contains a compound having isocyanate groups at two ends, and even more preferably contains a compound of a linear molecule having isocyanate groups at both ends. The urethane prepolymer (A) more preferably contains 90% by mass or more of a compound having isocyanate groups at two ends, and even more preferably contains 95% by mass or more. The urethane prepolymer (A) may be composed of a compound having isocyanate groups at two ends.

[0021] In the urethane prepolymer (A), the structure derived from the polyol includes a structure derived from the polycarbonate polyol and a structure derived from the polyether polyol. The structure derived from the polycarbonate polyol and the structure derived from the polyether polyol may be contained in different compounds or may be contained in one compound.

[0022] For example, the urethane prepolymer (A) may be a composition containing two or more types of compounds each having either a structure derived from a polycarbonate polyol or a structure derived from a polyether polyol, or a composition containing a compound having both a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, or a composition containing three or more types of compounds.

[0023] The urethane prepolymer (A) preferably contains two or more compounds each having one of a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, that is, the urethane prepolymer (A) preferably contains a polycarbonate polyol having an isocyanate group at least at either end, and a polyether polyol having an isocyanate group at least at either end.

[0024] The urethane prepolymer (A) may contain, for example, a compound having a structure derived from a polycarbonate polyol, a structure derived from a polyether polyol, and a structure derived from a polyisocyanate between these structures.

[0025] [Structure derived from polycarbonate polyol] The structure derived from the polycarbonate polyol in the urethane prepolymer (A) can improve the reliability and adhesive strength of the adhesive composition after a moisture reaction. The structure derived from the polycarbonate polyol has, for example, a structure derived from a polyhydric alcohol and a structure derived from a carbonate ester.

[0026] The structure derived from the polycarbonate polyol contained in the urethane prepolymer (A) preferably contains a structure derived from a linear divalent polycarbonate polyol. The proportion of the structure derived from the linear divalent polycarbonate polyol in the structure derived from the polycarbonate polyol contained in the urethane prepolymer (A) is preferably 90% by mass or more, more preferably 95% by mass or more. The structure derived from the polycarbonate polyol contained in the urethane prepolymer (A) may be composed of a structure derived from a linear divalent polycarbonate polyol.

[0027] As the carbonate ester, for example, dimethyl carbonate, diethyl carbonate, cyclocarbonate, diphenyl carbonate, etc. These compounds may be used alone or in combination of two or more kinds.

[0028] The polyhydric alcohol is preferably a dihydric alcohol. In addition to 1,6-hexanediol and 1,5-pentanediol, examples of the dihydric alcohol include aliphatic or alicyclic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, isomers of butanediol, isomers of pentanediol, neopentyl glycol, isomers of hexanediol, 2-methylpropanediol, 2,4,4-trimethyl-1,6-hexanediol, 2,2,4-trimethyl-1,6-hexanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. The polyhydric alcohol may be used alone or in combination of two or more.

[0029] The structure derived from the polycarbonate polyol preferably contains a structure derived from a crystalline polycarbonate polyol. The crystalline polycarbonate polyol is a polycarbonate polyol that forms crystals at 25° C. The structure derived from the crystalline polycarbonate polyol may contain only one type, or may contain two or more types.

[0030] The number average molecular weight (Mn) of the crystalline polycarbonate polyol is preferably 500 or more, more preferably 800 or more, even more preferably 1200 or more, and particularly preferably 1600 or more. This is because the high temperature and high humidity reliability and initial adhesion of the part bonded by the adhesive composition are improved. The number average molecular weight (Mn) of the crystalline polycarbonate polyol is preferably 5000 or less, more preferably 3000 or less, and even more preferably 2500 or less. This is because the viscosity of the adhesive composition is not too high. The number average molecular weight is a polystyrene equivalent value measured by gel permeation chromatography (GPC), and specifically, is a value measured under the following conditions.

[0031] Measuring device: Hitachi High-Tech Corporation Chromaster MODEL CMORG, CM5456 Columns: "Gelpack GLA130-S", "Gelpack GLA150-S" and "Gelpack GLA160-S" (Hitachi Chemical Co., Ltd., HPLC packed columns) Eluent: Tetrahydrofuran Flow rate: 1.0mL / min Column temperature: 40℃ Detector: RI Sample volume: 0.07mL Sample concentration: 1% by mass

[0032] The structure derived from the polycarbonate polyol may include a structure derived from a liquid polycarbonate polyol. The liquid polycarbonate polyol is a polycarbonate polyol that is neither crystallized nor vitrified at 25° C. The structure derived from the liquid polycarbonate polyol may include only one type, or may include two or more types.

[0033] The structure derived from the polycarbonate polyol may include a structure derived from an amorphous polycarbonate polyol. The amorphous polycarbonate polyol is a non-crystalline polycarbonate polyol having a glass transition temperature of 25° C. or higher. The structure derived from the amorphous polycarbonate polyol may include only one type, or may include two or more types.

[0034] The number average molecular weight (Mn) of the liquid polycarbonate polyol and the amorphous polycarbonate polyol is preferably 500 or more, more preferably 800 or more, even more preferably 1200 or more, and particularly preferably 1600 or more. This is to improve reliability and adhesiveness under high temperature and high humidity. The number average molecular weight (Mn) of the liquid polycarbonate polyol and the amorphous polycarbonate polyol is preferably 5000 or less, more preferably 3000 or less, and even more preferably 2500 or less. This is to prevent the viscosity of the adhesive composition from becoming too high. The number average molecular weight is a polystyrene equivalent value measured by gel permeation chromatography (GPC), and the specific measurement method is as described above.

[0035] From the viewpoint of further improving the adhesiveness of the adhesive composition, the ratio of the structure derived from the polycarbonate polyol in the structure derived from the polyol in the urethane prepolymer (A) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. From the viewpoint of suppressing an increase in the viscosity of the adhesive composition, the ratio of the structure derived from the polycarbonate polyol in the structure derived from the polyol in the urethane prepolymer (A) is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.

[0036] From the viewpoint of further improving the adhesiveness of the adhesive composition, the ratio of the structure derived from the crystalline polycarbonate polyol in the structure derived from the polyol in the urethane prepolymer (A) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. From the viewpoint of suppressing an increase in the viscosity of the adhesive composition, the ratio of the structure derived from the polycarbonate polyol in the structure derived from the polyol in the urethane prepolymer (A) is preferably 95% by mass or less, more preferably 85% by mass or less, and even more preferably 75% by mass or less.

[0037] [Structure derived from polyether polyol] The structure derived from the polyether polyol in the urethane prepolymer (A) suppresses an increase in the melt viscosity of the adhesive composition and makes it possible to adjust the open time after application, thereby improving the workability of the bonding process.

[0038] The structure derived from the polyether polyol contained in the urethane prepolymer (A) has a structure derived from a polyhydric alcohol. The raw material for obtaining the structure derived from the polyhydric alcohol is not limited to polyhydric alcohol, and for example, a compound having a plurality of epoxy groups may be used as long as it has the same structure. The structure derived from the polyether polyol contained in the urethane prepolymer (A) preferably includes a structure derived from a linear divalent polyether polyol. In the urethane prepolymer (A), the proportion of the structure derived from the linear divalent polyether polyol in the structure derived from the polyether polyol is preferably 90 mass% or more, more preferably 95 mass% or more. In the urethane prepolymer (A), the structure derived from the polyether polyol may be composed of a structure derived from a linear divalent polyether polyol.

[0039] Examples of polyether polyols from which the compounds contained in the urethane prepolymer (A) are derived include polyethylene glycol, polypropylene glycol, polybutylene glycol, polytetramethylene glycol, and ethylene oxide-modified polypropylene glycol. The polyether polyols may be used alone or in combination of two or more.

[0040] From the viewpoints of high adhesive strength and an appropriate open time after application, the number average molecular weight Mn of the polyether polyol is preferably 500 or more, more preferably 800 or more, even more preferably 1200 or more, and particularly preferably 1600 or more. From the viewpoints of suppressing an increase in viscosity of the adhesive composition, the number average molecular weight Mn of the polyether polyol is preferably 10000 or less, more preferably 7000 or less, and even more preferably 4000 or less, from the viewpoints of adhesiveness and an appropriate open time after application.

[0041] In the urethane prepolymer (A), the proportion of the polyether polyol-derived structure in the polyol-derived structure is preferably 90 mass% or less, more preferably 80 mass% or less, and even more preferably 70 mass% or less, from the viewpoints of suppressing an increase in the melt viscosity of the adhesive composition and improving the initial adhesive strength to an adherend and the adhesive strength after curing. From the same viewpoint, the proportion of the polyether polyol-derived structure in the polyol-derived structure in the urethane prepolymer (A) is preferably 5.0 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more.

[0042] The urethane prepolymer (A) may contain, as a structure derived from a polyol, a structure derived from a polyol other than a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol. However, in order to obtain high reliability under high temperature and high humidity conditions, it is preferable not to contain a structure derived from a polyester polyol, but the urethane prepolymer (A) may contain a structure derived from a polyester polyol within a range in which the reliability is not significantly reduced.

[0043] [Structure derived from polyisocyanate] The structure derived from the polyisocyanate in the urethane prepolymer (A) is not particularly limited as long as it is a structure derived from a compound having a plurality of isocyanate groups.

[0044] Examples of the polyisocyanate contained in the urethane prepolymer (A) include aromatic polyisocyanates such as diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, and p-phenylene diisocyanate; alicyclic polyisocyanates such as dicyclohexylmethane diisocyanate and isophorone diisocyanate; linear polyisocyanates such as hexamethylene diisocyanate; and other aliphatic polyisocyanates.

[0045] In the urethane prepolymer (A), the structure derived from the polyisocyanate preferably contains a structure derived from a compound having two isocyanate groups (diisocyanate). In the urethane prepolymer (A), the proportion of the structure derived from the compound having two isocyanate groups in the structure derived from the polyisocyanate is preferably 90% by mass or more, more preferably 95% by mass or more. In the urethane prepolymer (A), the structure derived from the polyisocyanate may be composed of a structure derived from a compound having two isocyanate groups.

[0046] From the viewpoints of reactivity and adhesiveness, the urethane prepolymer (A) preferably contains a structure derived from an aromatic diisocyanate as a structure derived from a polyisocyanate, and more preferably contains a structure derived from diphenylmethane diisocyanate. The structure derived from a polyisocyanate may contain only one type of structure, or may contain two or more types of structures.

[0047] [Example 1 of urethane prepolymer (A)] In one preferred embodiment of the present invention, the urethane prepolymer (A) contains, as a structure derived from a polyol, a structure derived from a crystalline polycarbonate polyol and a structure derived from a liquid polyether polyol. Here, the crystalline polycarbonate polyol is as described above, and the liquid polyether polyol is a polyether polyol that has not been crystallized or vitrified at 25°C.

[0048] In one example of this, in the urethane prepolymer (A), the proportion of structures derived from crystalline polycarbonate polyol in the structures derived from polyol is 50% by mass or more and 80% by mass or less, and the proportion of structures derived from liquid polyether polyol in the structures derived from polyol is 15% by mass or more and 45% by mass or less.

[0049] In this example of the urethane prepolymer (A), it is more preferable that the proportion of structures derived from crystalline polycarbonate polyol in the structures derived from polyol is 60% by mass or more and 80% by mass or less, and the proportion of structures derived from liquid polyether polyol in the structures derived from polyol is 20% by mass or more and 40% by mass or less.

[0050] In the urethane prepolymer (A) according to this example, the content of structures derived from polyols other than the structures derived from crystalline polycarbonate polyols and the structures derived from liquid polyether polyols is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, and even more preferably 1.0 mass% or less, based on the total structures derived from polyols. In the urethane prepolymer (A) according to this example, the structures derived from polyols may be composed of the structures derived from crystalline polycarbonate polyols and the structures derived from liquid polyether polyols.

[0051] The adhesive composition containing the urethane prepolymer (A) according to this configuration example can form an adhesive layer that has high adhesive strength and is highly reliable under high temperature and high humidity, high temperature, low temperature conditions, and when subjected to thermal shock.

[0052] [Example 2 of urethane prepolymer (A)] In another preferred configuration example of this embodiment, in the urethane prepolymer (A), the proportion of structures derived from polycarbonate polyol among the structures derived from polyol is 20 mass% or more and 60 mass% or less, and the proportion of structures derived from polyether polyol among the structures derived from polyol is 40 mass% or more and 80 mass% or less.

[0053] In this example of the urethane prepolymer (A), it is more preferable that the proportion of structures derived from polycarbonate polyol in the structures derived from polyol is 30% by mass or more and 50% by mass or less, and the proportion of structures derived from polyether polyol in the structures derived from polyol is 50% by mass or more and 70% by mass or less.

[0054] In this example of the urethane prepolymer (A), the proportion of structures derived from crystalline polycarbonate polyol in the structures derived from polycarbonate polyol is preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 100% by mass.

[0055] In this example of the urethane prepolymer (A), the proportion of structures derived from liquid polyether polyol in the structures derived from polyether polyol is preferably 30% by mass or more and 70% by mass or less, and more preferably 40% by mass or more and 60% by mass or less.

[0056] In the urethane prepolymer (A) according to this example, the content of structures derived from polyols other than the structures derived from polycarbonate polyols and the structures derived from polyether polyols is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, and even more preferably 1.0 mass% or less, based on the total structures derived from polyols. In the urethane prepolymer (A) according to this example, the structures derived from polyols may be composed of structures derived from polycarbonate polyols and structures derived from polyether polyols.

[0057] According to the adhesive composition containing the urethane prepolymer (A) of this configuration example, it is possible to form an adhesive layer that is flexible and has high adaptability to deformation, that is, has a low elastic modulus and high elongation.

[0058] [Method of synthesizing urethane prepolymer (A)] The urethane prepolymer (A) can be synthesized, for example, by reacting a polyol with a polyisocyanate, but is not limited to this method. The reaction temperature of the polyol with the polyisocyanate may be, for example, 85 to 120°C.

[0059] When synthesizing the urethane prepolymer (A) by this method, the ratio of the isocyanate group (NCO) equivalent of the polyisocyanate to the hydroxyl group (OH) equivalent of the polyol, NCO / OH, is preferably 1.8 or more, more preferably 1.9 or more, and even more preferably 1.95 or more. This is because a larger amount of polyurethane having a plurality of isocyanate groups, i.e., the urethane prepolymer (A), can be obtained. Furthermore, this is because the viscosity of the obtained urethane prepolymer (A) is prevented from increasing, and the workability is easily improved. In addition, NCO / OH is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.2 or less. This is because foaming during the moisture curing reaction of the adhesive composition can be suppressed, and the adhesiveness is further improved.

[0060] [Hindered phenol antioxidant (B)] The hindered phenol-based antioxidant (B) improves the heat resistance reliability of the bonded joint formed by the adhesive composition. The hindered phenol-based antioxidant (B) is a compound having a hydroxyl group (phenolic hydroxyl group) bonded to a benzene ring, and having a structure in which a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom bonded to the hydroxyl group in the benzene ring to which the hydroxyl group is bonded.

[0061] The hindered phenol-based antioxidant (B) is preferably a compound having a plurality of phenolic hydroxyl groups in one molecule, more preferably a compound having three or more phenolic hydroxyl groups in one molecule, and most preferably a compound having four phenolic hydroxyl groups in one molecule. In the hindered phenol-based antioxidant (B), it is preferable that one phenolic hydroxyl group is present per one benzene ring.

[0062] In the benzene ring in the hindered phenol antioxidant (B) to which a hydroxyl group is bonded, a tertiary carbon atom is preferably bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded, and more preferably a tertiary carbon atom is bonded to both of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded, in order to appropriately adjust the steric hindrance of the hydroxyl group bonded to the benzene ring.

[0063] In the benzene ring to which the hydroxyl group in the hindered phenol antioxidant (B) is bonded, it is more preferable that a tert-butyl group is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded, and it is particularly preferable that tert-butyl groups are bonded to both of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded. This is to appropriately adjust the steric hindrance of the hydroxyl group bonded to the benzene ring. This is to appropriately adjust the steric hindrance of the hydroxyl group bonded to the benzene ring.

[0064] Examples of the hindered phenol antioxidant (B) include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl]propionate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 4,4 Examples of the hindered phenol antioxidant (B) include ',4''-(1-methylpropanyl-3-ylidene)tris(6-tert-butyl-m-cresol), 6,6'-di-tert-butyl-4,4'-butylidene di-m-cresol, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene. The hindered phenol antioxidant (B) may be composed of one type of compound, or may contain two or more types of compounds.

[0065] In the adhesive composition, the content of the hindered phenol-based antioxidant (B) relative to 100 parts by mass of the urethane prepolymer (A) is preferably 0.10 parts by mass or more, more preferably 0.20 parts by mass or more, and even more preferably 0.30 parts by mass or more, in order to further improve the heat resistance reliability of the bonded joint formed by the adhesive composition.

[0066] In the adhesive composition, the content of the hindered phenol-based antioxidant (B) relative to 100 parts by mass of the urethane prepolymer (A) is preferably 2.0 parts by mass or less, more preferably 1.0 part by mass or less, and even more preferably 0.50 parts by mass or less, in order to improve the adhesive strength of the adhesive composition by suppressing the content of non-reactive components.

[0067] [Other ingredients] In order to accelerate the curing of the adhesive composition and to further enhance the adhesiveness, the adhesive composition according to the present embodiment may further contain a catalyst, such as dibutyltin dilaurate, dibutylthione octate, dimethylcyclohexylamine, dimethylbenzylamine, and trioctylamine.

[0068] From the viewpoint of imparting stronger adhesiveness to the adhesive composition, the adhesive composition according to the present embodiment may further contain a tackifier resin, such as a rosin resin, a rosin ester resin, a hydrogenated rosin ester resin, a terpene resin, a terpene phenol resin, a hydrogenated terpene resin, a petroleum resin, a hydrogenated petroleum resin, a coumarone resin, a ketone resin, a styrene resin, a modified styrene resin, a xylene resin, or an epoxy resin.

[0069] The adhesive composition according to this embodiment may contain antioxidants other than the hindered phenol-based antioxidant (B), pigments, dyes, ultraviolet absorbers, surfactants, flame retardants, fillers, and the like, as necessary.

[0070] [Total content of urethane prepolymer (A) and hindered phenol-based antioxidant (B) in adhesive composition] The total content of the urethane prepolymer (A) and the hindered phenol-based antioxidant (B) in the adhesive composition is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more. This is because an adhesive composition having high flexibility and capable of reliable adhesion in high-temperature and high-humidity environments can be obtained. The adhesive composition according to this embodiment may be composed of the urethane prepolymer (A) and the hindered phenol-based antioxidant (B).

[0071] [Method of manufacturing adhesive composition] The adhesive composition according to the present embodiment can be produced, for example, by a method including a step of reacting a polyol with a polyisocyanate to obtain a urethane prepolymer (A) having an isocyanate group at the end of a structure derived from the polyol. The step of obtaining the urethane prepolymer (A) is as described in the section on the synthesis method of the urethane prepolymer (A).

[0072] The hindered phenol-based antioxidant (B) may be added before reacting the polyol with the polyisocyanate, during the reaction, or after the urethane prepolymer (A) is synthesized.

[0073] [Melt viscosity of adhesive composition] The melt viscosity of the adhesive composition is a value measured by a rotational viscometer at 120°C, and will be specifically described later in the Examples. From the viewpoint of improving application workability, the melt viscosity of the adhesive composition is preferably 20 Pa·s or less, more preferably 15 Pa·s or less, and even more preferably 11 Pa·s or less, and may be 8.0 Pa·s or less, or may be 5.0 Pa·s or less. From the same viewpoint, the melt viscosity of the adhesive composition is preferably 0.2 Pa·s or more, and more preferably 0.5 Pa·s or more.

[0074] [Adhesion method using adhesive composition] Various members can be bonded using the adhesive composition according to the present embodiment. The bonding method according to the present embodiment includes, for example, a coating step of coating a molten adhesive composition on a first member, a mounting step of mounting a second member on the surface of the first member on which the adhesive composition is applied, and a reaction step of reacting the applied adhesive composition in air containing moisture, but is not limited to these steps. For example, the adhesive composition may be applied to the bonding surfaces of both the first member and the second member.

[0075] The method of applying the adhesive composition is not particularly limited, but for example, the adhesive composition can be applied while being discharged from an air dispenser. In this case, from the viewpoint of workability, it is preferable that the adhesive composition be heated to 80 to 130°C before being discharged.

[0076] The relative humidity of the air in the step of reacting the adhesive composition is preferably 20% RH or more, more preferably 30% RH or more, and even more preferably 40% RH or more, in order to improve the reaction speed of the adhesive composition and achieve strong adhesion in a shorter time.

[0077] Examples of materials that can be bonded with the adhesive composition of this embodiment include metals and alloys such as SUS and aluminum, polymeric materials such as polycarbonate, polyamide, and polybutylene terephthalate, and inorganic materials such as glass and metal oxides. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0079] [Examples 1 to 5, Comparative Examples 1 to 2] The polyol and the hindered phenol-based antioxidant (B), which had been dehydrated in advance using a vacuum dryer, were uniformly mixed in the types and amounts (parts by mass) shown in Table 1, and then diphenylmethane diisocyanate (MDI) was further added and mixed uniformly. These mixing steps were carried out at 100°C. The resulting mixture was then reacted at 110°C for 1 hour, and further stirred at 110°C for 1 hour under reduced pressure and degassing to obtain an adhesive composition.

[0080] The properties of each of the adhesive compositions obtained in Examples 1 to 5 and the compositions obtained in Comparative Examples 1 and 2 were evaluated as follows. The results are shown in Table 1.

[0081] (Melt Viscosity) The melt viscosity [Pa·s] of the adhesive composition (sample amount: 15 g) was measured at 120°C with a No. 4 rotor using a TVB-25H viscometer (manufactured by Toki Sangyo Co., Ltd.) at a rotor rotation speed of 20 rpm.

[0082] (Mechanical properties) The adhesive composition melted at 100°C was applied onto a resin film, and then cooled at a temperature of 25°C and a relative humidity of 50%RH for 24 hours to form a film with a thickness of 100 μm. The formed film was cut out so as to have a No. 1 dumbbell shape as specified in JIS K 6251 in plan view. That is, the cut-out shape here has the above-mentioned No. 1 dumbbell shape in plan view and a thickness of 100 μm. The cut-out film was placed in a thermo-hygrostat at a temperature of 25°C and a relative humidity of 50%RH for 7 days to prepare a measurement sample. The tensile modulus (MPa) and elongation (%) of this sample were measured in accordance with JIS K-6251.

[0083] [Adhesive strength (shear strength)] FIG. 1 is a plan view showing a test piece (adhesion test piece) for measuring the adhesive strength of an adhesive composition. The up-down direction in FIG. 1 is the vertical direction, and the left-right direction in FIG. 1 is the horizontal direction. The adhesive composition is melted at 100° C. and applied to a polycarbonate (PC) substrate 1 having a length of 25 mm, a width of 75 mm, and a thickness of 2 mm in an environment of a temperature of 23° C. and a relative humidity of 50% RH. The adhesive composition is applied over the entire vertical direction of the substrate 1 (i.e., a length of 25 mm) with a vertical straight line 4 located 10 mm to the right of the left end (vertical side) 11 of the substrate 1 as the center.

[0084] A PC substrate 2 measuring 25 mm long x 75 mm wide x 2 mm thick was pressed onto the surface of the substrate 1 on which the adhesive composition had been applied, sandwiching the adhesive composition therebetween, to prepare an adhesion test specimen. In the obtained adhesion test specimen, the left end 11 of the substrate 1 and the right end (vertical side) 21 of the substrate 2 were disposed with a straight line 4 in between, and the distance between the right end 21 and the straight line 4 was 10 mm.

[0085] In addition, when the substrates were pressed against each other, two spacers 31 and 32 of the same shape were sandwiched between the substrate 1 and the substrate 2. The spacers 31 and 32 were both rectangular plates with a thickness of 0.10 mm. The two spacers 31 and 32 were arranged on both the left and right sides of the applied adhesive composition so as not to come into contact with the adhesive composition, and were arranged so that the vertical center line of the spacer 31 coincided with the left end 11 of the substrate 1, and the vertical center line of the spacer 32 coincided with the right end 21 of the substrate 2, respectively.

[0086] The adhesive test piece was left to stand for one day in an environment of temperature 23°C and relative humidity 50%RH. In this way, an adhesive layer 4 of length 25 mm × width 1 mm × thickness 0.10 mm was formed between the substrate 1 and the substrate 2. In the obtained adhesive test piece, the right end 12 of the substrate 1 was pulled rightward and the left end 22 of the substrate 2 was pulled leftward, and a shear test (pulling speed: 10 mm / min) was performed to determine the adhesive strength (MPa).

[0087] [Reliability] The adhesive test pieces (Fig. 1) prepared in the same manner as in the measurement of adhesive strength were left to stand under the following conditions. Next, in each test, the adhesive test pieces were left to stand for one day in an environment of a temperature of 23°C and a relative humidity of 50% RH. After that, the same test as in the measurement of adhesive strength above (tensile speed: 10 mm / min) was performed on these adhesive test pieces to determine the adhesive strength (MPa). High temperature and humidity test 2000 hours under conditions of 85℃ temperature and 85% relative humidity. High temperature testing 2000 hours at 95℃. Low temperature test 2000 hours at -40℃ -Thermal shock test Using a thermal shock device (Espec Corp. TSE-11-A), 1000 cycles were performed, with one cycle being 85°C for 30 minutes and -40°C for 30 minutes.

[0088] [Table 1] *The materials in Table 1 are as follows. T6002: Asahi Kasei polycarbonate diol (hydroxyl group number: 2, number average molecular weight 2000, crystalline, solid at 25°C (melting point: 40-50°C)) T5652: Asahi Kasei polycarbonate diol (hydroxyl group number: 2, number average molecular weight 2000, liquid at 25°C (melting point: -5°C or lower)) PTG2000: Polytetramethylene glycol manufactured by Hodogaya Chemical (number of hydroxyl groups: 2, number average molecular weight 2000, crystalline, solid at 25°C (melting point: 27°C)) PEG4000S: Polyethylene glycol manufactured by Sanyo Chemical Industries (number of hydroxyl groups: 2, number average molecular weight 3400, crystalline, solid at 25°C (melting point: 50-60°C)) PP2000: Polypropylene glycol manufactured by Sanyo Chemical Industries (number of hydroxyl groups: 2, number average molecular weight 2000, liquid at 25°C (melting point: -40 to -30°C)) C-1: Polyester of 1,6-hexanediol and adipic acid (number of hydroxyl groups: 2, number average molecular weight 2000, crystalline, solid at 25°C (melting point: 50-60°C)) C-2: Polyester of neopentyl glycol, ethylene glycol, and isophthalic acid (number of hydroxyl groups: 2, number average molecular weight 2000, liquid at 25°C (glass transition point: -15°C)) MDI: Diphenylmethane diisocyanate (number of isocyanate groups: 2, manufactured by Nippon Polyurethane Industry: Millionate MT) IN1010: Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl]propionate (BASF Japan Ltd.: Irganox 1010)

[0089] [Evaluation Results] The adhesive joints formed using the adhesive compositions according to Examples 1 to 4 all exhibited low tensile modulus and large elongation, and maintained high adhesive strength even in a high-temperature, high-humidity environment. Therefore, it is clear that the adhesive compositions according to the above examples are highly flexible and capable of providing highly reliable adhesion in a high-temperature, high-humidity environment.

[0090] The composition according to Comparative Example 1, which does not have a structure derived from a polycarbonate polyol as the structure derived from the polyol in the urethane prepolymer (A), and the composition according to Comparative Example 2, which does not have a structure derived from a polyether polyol as the structure derived from the polyol in the urethane prepolymer (A), were both unable to maintain sufficient adhesive strength under high temperature and high humidity conditions. In addition, the composition according to Comparative Example 3, which does not contain a hindered phenol-based antioxidant (B), was unable to maintain sufficient adhesive strength under high temperature and high humidity conditions. Furthermore, the composition according to Comparative Example 3 was also unable to maintain sufficient adhesive strength under high temperature conditions and when repeatedly subjected to thermal shock.

[0091] From the above, it can be seen that a reactive hot melt adhesive composition comprising a urethane prepolymer (A) and a hindered phenol-based antioxidant (B), in which the urethane prepolymer (A) is composed of a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from the polyol, the structure derived from the polyol including a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, and the hindered phenol-based antioxidant (B) is a compound having a hydroxyl group bonded to a benzene ring, and a structure in which, in the benzene ring to which the hydroxyl group is bonded, a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded, has high flexibility and is capable of providing highly reliable adhesion even in high-temperature and high-humidity environments.

[0092] Furthermore, it can be seen that a bonding method having an application step of applying the adhesive composition according to each example to a first member, an attachment step of attaching a second member to the surface of the first member on which the adhesive composition has been applied, and a reaction step of reacting the applied adhesive composition in moisture-containing air enables bonding that is highly flexible and highly reliable even in high-temperature and high-humidity environments.

Claims

1. A reactive hot melt adhesive composition comprising a urethane prepolymer (A) and a hindered phenol-based antioxidant (B), The urethane prepolymer (A) comprises a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from a polyol, The structure derived from the polyol includes a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, The hindered phenol-based antioxidant (B) is a compound having a hydroxyl group bonded to a benzene ring, and a structure in which a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded in the benzene ring.

2. The reactive hot melt adhesive composition according to claim 1, wherein the urethane prepolymer (A) contains two or more compounds each having one of a structure derived from the polycarbonate polyol and a structure derived from the polyether polyol.

3. 2. The reactive hot melt adhesive composition according to claim 1, wherein the content of the hindered phenol-based antioxidant (B) is 0.10 parts by mass or more and 2.0 parts by mass or less relative to 100 parts by mass of the urethane prepolymer (A).

4. 3. The reactive hot melt adhesive composition according to claim 1, wherein the urethane prepolymer (A) contains a compound having a plurality of isocyanate groups at its terminals.

5. 3. The reactive hot melt adhesive composition according to claim 1, wherein the urethane prepolymer (A) contains a compound having two isocyanate groups at its two terminals.

6. 3. The reactive hot melt adhesive composition according to claim 1, wherein in the urethane prepolymer (A), a ratio of the structure derived from the polycarbonate polyol to the structure derived from the polyol is 10 mass% or more and 95 mass% or less.

7. 3. The reactive hot melt adhesive composition according to claim 1, wherein in the urethane prepolymer (A), a ratio of the structure derived from the polyether polyol to the structure derived from the polyol is 5.0 mass% or more and 90 mass% or less.

8. 3. The reactive hot melt adhesive composition according to claim 1, wherein the urethane prepolymer (A) has a structure derived from a crystalline polycarbonate polyol as a structure derived from the polycarbonate polyol, and the crystalline polycarbonate polyol is a polycarbonate polyol that forms crystals at 25°C.

9. The reactive hot melt adhesive composition according to claim 8, wherein in the urethane prepolymer (A), a ratio of the structure derived from the crystalline polycarbonate polyol to the structure derived from the polyol is 10 mass% or more and 95 mass% or less.

10. The urethane prepolymer (A) contains, as the structure derived from the polyol, a structure derived from a crystalline polycarbonate polyol and a structure derived from a liquid polyether polyol, The crystalline polycarbonate polyol is a polycarbonate polyol that forms crystals at 25°C. The liquid polyether polyol is a polyether polyol that is neither crystallized nor vitrified at 25°C, 3. The reactive hot melt adhesive composition according to claim 1, wherein in the urethane prepolymer (A), the proportion of structures derived from crystalline polycarbonate polyol in the structures derived from the polyol is 50% by mass or more and 80% by mass or less, and the proportion of structures derived from liquid polyether polyol in the structures derived from the polyol is 15% by mass or more and 45% by mass or less.

11. 3. The reactive hot melt adhesive composition according to claim 1, wherein in the urethane prepolymer (A), a ratio of structures derived from the polycarbonate polyol among the structures derived from the polyol is 20% by mass or more and 60% by mass or less, and a ratio of structures derived from the polyether polyol among the structures derived from the polyol is 40% by mass or more and 80% by mass or less.

12. applying a molten reactive hot melt adhesive composition to a first member; a mounting step of mounting a second member on the surface of the first member on which the reactive hot melt adhesive composition is applied; A reaction step of reacting the applied reactive hot melt adhesive composition in moisture-containing air, The reactive hot melt adhesive composition comprises a urethane prepolymer (A) and a hindered phenol-based antioxidant (B), The urethane prepolymer (A) comprises a compound having a structure derived from a polyol and an isocyanate group at at least one end of the structure derived from a polyol, The structure derived from the polyol includes a structure derived from a polycarbonate polyol and a structure derived from a polyether polyol, The hindered phenol-based antioxidant (B) is a compound having a hydroxyl group bonded to a benzene ring, and a structure in which a secondary or higher carbon atom is bonded to at least one of the carbon atoms adjacent to the carbon atom to which the hydroxyl group is bonded in the benzene ring.

Citation Information

Patent Citations

  • Moisture-curable polyurethane hot-melt resin composition, adhesive, and article

    JP2020094085A

  • Moisture-curable polyurethane hot-melt resin composition, adhesive, and article

    JP2020097650A